(untitled) (Research, Society and Development, 2020)
The objective of this work was to perform the thermographic evaluation of the mammary glands and the eyeball of dairy cattle females on a rural property in the municipality of Mojuí dos Campos, in Western Pará. Eight (n = 8) pluriparous Girolando dairy females were used, maintained in a semi-intensive system, with an average age and weight of 7 years and 450 kg, respectively. The females were divided into two experimental groups, Lactating (LACT, n = 4) and Non-Lactating (N-LACT, n = 4). An infrared thermographic camera was used to obtain the surface temperature of the mammary glands (upper, middle and final third region) and the eyeball. Past version 2.16 was used, obtaining mean and standard deviation and analysis of variance with the Anova One-Waye Tukey test (5%). Mean surface temperature was observed in the mammary glands in the LACT and N-LACT group of 40.2ºC±0.8 and 39.6ºC±0.9, 38.9ºC±0.6 and 38.0ºC±0.7, and 37.5ºC±0.6 and 36.8ºC±0.7 in the upper, middle and final third regions, respectively. The females in the N-LACT group had an average temperature of the eyeball of 36.3ºC ± 0.8 and the LACT 37.3ºC±0.8. There was a numerically higher surface temperature in the mammary gland of lactating females, especially in the upper third, and lower temperatures in the final third (teats), however, statistically significant differences were not detected between the groups (P≥0.05). Greater thermal amplitude was found in the middle third of the mammary glands and higher surface temperature in the eyeball region of lactating females. Thus, infrared thermography is a technique capable of pointing out specific regions in the detection of changes in dairy cattle herds.